Limb salvage of the foot with Lisfranc amputation following squamous cell carcinoma. Issue 7 (June 2019) - Dahle, Sara E; Martin, Kennon; Williams, John C; Tchanque-Fossuo, Catherine N; West, Kaitlyn IM; Schulman, Joshua M
The indolent character of squamous cell carcinoma of the foot can be misleading and might result in unwarranted excisions or delayed treatment.